Effects of a standard operating procedure on prehospital emergency care of patients presenting with symptoms of the acute coronary syndrome - Francis, Roland C. E.; Bubser, Florian; Schmidbauer, Willi; Spies, Claudia D.; Soerensen, Marc; Bosse, Goetz; Kerner, Thoralf (European Journal of Emergency Medicine, 2014)
To determine whether a standard operating procedure (SOP) for prehospital management of patients with the acute coronary syndrome (ACS) improves the quality of patient care in terms of adherence to treatment guidelines of the European Society of Cardiology. Among a total of 1025 patient medical records collected from a period before and after the introduction of the SOP, 269 records included the working diagnosis of ACS and were then reviewed for guideline adherence. Most aspects of patient evaluation, monitoring, treatment, and hospital allocation were fairly guideline adherent (>70%) before the SOP was introduced and were not affected by the SOP. The percentage of cases in whom sublingual nitrate (55.2 vs. 66.7%) or intravenous morphine (26.9 vs. 43.0%) was administered without contraindications was higher after the SOP had been introduced. Therefore, the use of an SOP in prehospital emergency medicine can partly improve the adherence to guideline recommendations for the treatment of patients with ACS. © 2014 Wolters Kluwer Health | Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2022-11-17
Keywords: acute coronary syndrome; emergency medicine; guideline adherence; standard